Features of marketing research in the mass media business - Shevchenko, Tatyana (Management and Entrepreneurship: Trends of Development, 2020)
The purpose of this study is to examine the tools and methods that mass media organizations use at the present stage to conduct marketing research of the target audience - to find out their needs, interests, expectations, assessments regarding the media products they consume; аnd also studying of a question of necessity and importance of carrying out qualitative marketing researches in the mass media organizations.  Analysis, synthesis, observation and comparison methods were used in the study. We have considered the tools and methods used to organize marketing research in the media business, demonstrate their specificity. After all, media products differ from other product categories in marketing in terms of audience perception. It is shown that the need and importance of studying the media needs of the audience by a mass media organization is provided by the functioning of the media not only as a business but also as a social institution that aims to ensure the joint activities of people. It is substantiated that clarifying the needs, interests, expectations, assessments of the audience regarding media products for mass media organizations are extremely important as for no other organization, as for no other business.JEL Classification: А12, А13, А14, М31